Г. Радбрух про ціннісну природу права - Дудченко, Валентина Віталіївна; Дудченко, Валентина Витальевна; Dudchenko, Valentina (My University, 2013)
Analyzed the main themes of the philosophical doctrine of the law of Radbruch, namely the methodology of law, facts and values, the value of the nature of law, law and ethics, the purpose of the law, private and public law, legal State, statutory lawlessness and supra-statutory law. All the themes of the teachings have been composed by Radbruch formula, according to which lawlessness will remain lawlessness, even if it is shaped in the form of law.
Дудченко В. В. Г. Радбрух про ціннісну природу права / В. В. Дудченко // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 123-131.
Keywords: факти і цінності; цінність природи права; право і етика; мета у праві; правова держава; законне право і надзаконне право; факты и ценности; ценность природы права; право и этика; цель в праве; правовое государство; законное право и надзаконное право; facts and values; the value of the nature of law; law and ethics; the purpose of the law; legal State; statutory lawlessness and supra-statutory law